2020
DOI: 10.1177/0964528420961393
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for post-operative cognitive dysfunction: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective: Post-operative cognitive dysfunction (POCD) is a common post-surgical complication, which is associated with increased costs and extended hospital stays. Recently, interest in acupuncture as a potential therapy for POCD has grown. The objective of this meta-analysis was to assess the effectiveness of acupuncture for POCD. Methods: PubMed, Embase, CENTRAL, Medline, Web of Science, CNKI, Wanfang, and VIP databases were searched through March 2018. Randomized controlled trials (RCTs) in which patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Acupuncture can not only promote the regeneration and repair of synapses and improve the function of the central nervous system [12] but also stimulate the cerebral cortex through the skull, improve the brain function under pathological conditions [13], and promote the cortex around the cerebral ischemic area. e high expression of synaptophysin accelerates the reconstruction of nerve function [14]. Current research results show that human cognitive function is highly correlated with the cortex such as the frontal lobe, temporal lobe, and parietal lobe [15].…”
Section: Discussionmentioning
confidence: 97%
“…Acupuncture can not only promote the regeneration and repair of synapses and improve the function of the central nervous system [12] but also stimulate the cerebral cortex through the skull, improve the brain function under pathological conditions [13], and promote the cortex around the cerebral ischemic area. e high expression of synaptophysin accelerates the reconstruction of nerve function [14]. Current research results show that human cognitive function is highly correlated with the cortex such as the frontal lobe, temporal lobe, and parietal lobe [15].…”
Section: Discussionmentioning
confidence: 97%
“…shows that acupuncture can effectively regulate the internal environment of the human body, so that the body has a higher level of defense ability, and the anesthesia effect is relatively significantly improved [6] . Through a large number of clinical studies, it is found that acupuncture at Baihui and Neiguan Points has a significant effect on improving brain hypoperfusion, enhancing brain metabolic function, enhancing brain blood flow and restoring brain nerve cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The 35 SRs/meta-analyses were published between 2007 and 2020. Thirty-two SRs/meta-analyses were conducted in China (Peng et al, 2007;Guo et al, 2008;Zhu and Zhang, 2009;Yuan and Zhang, 2010;Liu et al, 2011Liu et al, , 2015Liu et al, , 2018Tian et al, 2012;Cao et al, 2013Cao et al, , 2014Fang et al, 2014;Hu et al, 2014;Zhao et al, 2014;Lu et al, 2015;Mai and Zheng, 2015;Xu and Xie, 2015;Zhang et al, 2015;Zhou et al, 2015Zhou et al, , 2017Deng and Wang, 2016;Lin et al, 2016Lin et al, , 2017Xiong et al, 2016;Zou et al, 2016;Wan et al, 2017;Zhan et al, 2017;Li et al, 2018Li et al, , 2020Wu et al, 2018;Tang et al, 2020;Wang et al, 2020), and three SRs/metaanalyses were conducted in Korea (Lee et al, 2008;Kwon et al, 2018;Kim et al, 2019). Twenty-three SRs/meta-analyses (68%) were published in Chinese, and 12 (34%) were published in English.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%